Association between baseline abundance of Peptoniphilus, a Gram-positive anaerobic coccus, and wound healing outcomes of DFUs - Min, Kyung R.; Galvis, Adriana; Baquerizo Nole, Katherine L.; Sinha, Rohita; Clarke, Jennifer; Kirsner, Robert S.; Ajdic, Dragana (PloS one, 2020)
Diabetic foot ulcers (DFUs) lead to nearly 100,000 lower limb amputations annually in the United States. DFUs are colonized by complex microbial communities, and infection is one of the most common reasons for diabetes-related hospitalizations and amputations. In this study, we examined how DFU microbiomes respond to initial sharp debridement and offloading and how the initial composition associates with 4 week healing outcomes. We employed 16S rRNA next generation sequencing to perform microbial profiling on 50 samples collected from 10 patients with vascularized neuropathic DFUs. Debrided wound samples were obtained at initial visit and after one week from two DFU locations, wound bed and wound edge. Samples of the foot skin outside of the wounds were also collected for comparison. We showed that DFU wound beds are colonized by a greater number of distinct bacterial phylotypes compared to the wound edge or skin outside the wound. However, no significant microbiome diversity changes occurred at the wound sites after one week of standard care. Finally, increased initial abundance of Gram-positive anaerobic cocci (GPAC), especially Peptoniphilus (p < 0.05; n = 5 subjects), was associated with impaired healing; thus, GPAC's abundance could be a predictor of the wound-healing outcome.